A Curriculum of Love and Sexual Violence in Pondok Pesantren: The Reality versus the Rhetoric of Education - Zulfikri Zulfikri (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study aims to analyze the conceptualization of the Love Curriculum (Kurikulum Cinta) in Islamic boarding schools (pesantren) as a pedagogical paradigm grounded in the values of rahmah (compassion), mahabbah (love), and respect for human dignity; examine the dynamics of power relations and the reality of sexual violence within pesantren as social contexts influencing the effectiveness of value implementation; and formulate an Integrative Model of a Child-Protection-Based Love Curriculum as a pedagogical and institutional response to the challenge of sexual violence. This research employs a qualitative approach using field research methods. Data were collected through participant observation, in-depth interviews with kiai (religious leaders), teachers, dormitory supervisors, and students, as well as document analysis of curricula and internal institutional policies. Data were analyzed thematically and interpretively to identify patterns of value internalization, structures of power relations, and existing protection mechanisms within institutional practices. The findings reveal that the Love Curriculum operates as both a living curriculum and a hidden curriculum, manifested through the moral exemplarity of the kiai, habituation of ethical conduct (adab), and social solidarity within the boarding school environment. The internalization of compassionate values occurs culturally and relationally rather than through a formally structured subject. However, the strong hierarchical structure and culture of obedience may generate vulnerabilities if not supported by clear accountability mechanisms and reporting procedures. The integration of compassionate values with child protection principles has not yet been fully institutionalized in formal policies. Therefore, this study proposes an integrative model combining theological values, literacy on power relations, education on bodily boundaries and informed consent, and structured child protection systems to strengthen students’ safety and dignity within contemporary pesantren education